Athlete preparation: Beyond the basics - Hawley, J. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Advances in molecular biology during the past 20 years have allowed scientists to elucidate how endurance- and resistance-based exercise stimulate skeletal muscle remodelling (i.e., promote mitochondrial biogenesis and muscle hypertrophy). A growing field of interest directly arising from our understanding of the molecular bases of training adaptation is how nutrient availability alters the regulation of many contraction-induced events in muscle in response to exercise. Changes in energy availability (acute and chronic) and macronutrient composition alter the concentration of blood-borne substrates and hormones, causing marked perturbations in the storage profile of skeletal muscle and other insulin-sensitive tissues. In turn, muscle energy status exerts profound effects on resting fuel metabolism and patterns of fuel utilization during exercise, as well as acute regulatory processes underlying gene expression and cell signalling. As such, nutrient-exercise interactions have the potential to activate or inhibit many biochemical pathways with putative roles in training adaptation. This talk will focus on recent trends in athlete preparation that have employed dietary periodisation protocols to enhance training adaptation and improve performance in endurance sports.